Experimental Appeals to Intuition - Renia Gasparatou (Crítica)
Today, experimental philosophers challenge traditional appeals to intuition; they empirically collect folk intuitions and then use their findings to attack philosophers’ intuitions. However this movement is not uniform. Radical experimentalists criticize the use of intuitions in philosophy altogether and they have been mostly attacked. Contrariwise, moderate experimentalists imply that lay persons’ intuitions are somehow relevant to philosophical problems. Sometimes they even use folk intuitions in order to advance theoretical theses. In this paper I will try to challenge the so-called moderate experimental attempts to rely on intuition in order to promote philosophical theses.